2021
DOI: 10.3390/life11070668
|View full text |Cite
|
Sign up to set email alerts
|

Fascia Mobility, Proprioception, and Myofascial Pain

Abstract: The network of fasciae is an important part of the musculoskeletal system that is often overlooked. Fascia mobility, especially along shear planes separating muscles, is critical for musculoskeletal function and may play an important, but little studied, role in proprioception. Fasciae, especially the deep epimysium and aponeuroses, have recently been recognized as highly innervated with small diameter fibers that can transmit nociceptive signals, especially in the presence of inflammation. Patients with conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 53 publications
0
38
0
Order By: Relevance
“…The possible causes of myofascial pain have been discussed in several articles: in some experimental studies it was shown that the hypertonic saline solution can cause a more intense and longer lasting pain when injected in fascia than in muscle [ 32 , 33 ]. Langevin et al [ 34 , 35 , 36 ], have hypothesized that reiterated postures, sports, or repetitive motions may generate altered movement patterns, which increase the thickness of the tissue and in turn limiting the sliding between fascia layers. This situation would augment inflammation and pain increasing the stimulation of free nerve endings present in them.…”
Section: Discussionmentioning
confidence: 99%
“…The possible causes of myofascial pain have been discussed in several articles: in some experimental studies it was shown that the hypertonic saline solution can cause a more intense and longer lasting pain when injected in fascia than in muscle [ 32 , 33 ]. Langevin et al [ 34 , 35 , 36 ], have hypothesized that reiterated postures, sports, or repetitive motions may generate altered movement patterns, which increase the thickness of the tissue and in turn limiting the sliding between fascia layers. This situation would augment inflammation and pain increasing the stimulation of free nerve endings present in them.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the repetitive overhead rotational motion during spiking, serving, and blocking, it is well documented that volleyball players often develop excessive external rotation range, and limited internal rotation range. With repetitive movements and micro-trauma, connective tissues can experience deformation, structural changes and may have an altered feedback mechanism for peripheral senses, such as proprioception ( Chen et al, 2021 ; Langevin, 2021 ). A recent systematic review on the effects of rehabilitation of shoulder proprioception suggests a specificity to proprioception deficits ( Ager et al, 2021 ); meaning specific pathologies (shoulder instabilities or rotator cuff dysfunctions, for example) present with specific proprioception deficits.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a loose connective tissue rich in hyaluronic acid (HA) occurs between the deep fascia and the underlying epimysium, which again allows the gliding between the muscles and the deep fascia [ 84 , 85 ]. Remarkably, changes in viscoelasticity of the deep fascial system, accumulation of high-molecular-weight (HMW) chains of HA, and altered mobility of fascial adjacent layers have been recently emerging as important causes of fascial nociceptor activation and thus as possible “pain generators” in the MPS [ 62 , 64 , 86 , 87 , 88 , 89 ].…”
Section: A Brief Overview Of the Human Fascial System And Its Role As...mentioning
confidence: 99%
“…In recent years, some papers discussed strong morphological and functional evidence for a nociceptive capacity of deep fascia and thus its contribution to various painful musculoskeletal conditions [ 58 , 60 , 61 , 62 , 63 , 64 ]. Clinical trials on healthy human volunteers demonstrated that electrical high-frequency stimulation of TLF or injection of pain-inducing substances into the TLF evokes long-term potentiation-like pain amplification while generating pain sensations that are more intense and unpleasant when compared to subcutaneous and muscular tissue [ 58 , 104 , 105 , 106 , 107 ].…”
Section: A Brief Overview Of the Human Fascial System And Its Role As...mentioning
confidence: 99%
See 1 more Smart Citation